2020
DOI: 10.1038/s41598-020-58375-y
|View full text |Cite
|
Sign up to set email alerts
|

Snellenius manilae bracovirus suppresses the host immune system by regulating extracellular adenosine levels in Spodoptera litura

Abstract: Sufficient energy supply to the host immune system is important for resisting pathogens. Therefore, during pathogen infection, the host metabolism is reassigned from storage, growth, and development to the immune system. Previous studies in Drosophila melanogaster have demonstrated that systemic metabolic switching upon an immune challenge is activated by extracellular adenosine signaling, modulating carbohydrate mobilization and redistributing energy to the hemocytes. In the present study, we discovered that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The lower AdoR expression in the hemocyte of BmNPVinfected larvae suggested that BmNPV suppresses the AdoR expression for compromising the host immune defense. Since AdoR in insect hemocyte has known playing the important roles on energy metabolism and cellular immune responses upon the bacterial and virus infections (21,31) as well as hematopoiesis (32). Notably, the same patterns of AdoR expression in BmNPVinfected larvae and BmN cells always being lower than in AcMNPV infection were found.…”
Section: Adenosine Signaling Is Involved In Metabolic Induction Upon Baculovirus Infectionmentioning
confidence: 77%
“…The lower AdoR expression in the hemocyte of BmNPVinfected larvae suggested that BmNPV suppresses the AdoR expression for compromising the host immune defense. Since AdoR in insect hemocyte has known playing the important roles on energy metabolism and cellular immune responses upon the bacterial and virus infections (21,31) as well as hematopoiesis (32). Notably, the same patterns of AdoR expression in BmNPVinfected larvae and BmN cells always being lower than in AcMNPV infection were found.…”
Section: Adenosine Signaling Is Involved In Metabolic Induction Upon Baculovirus Infectionmentioning
confidence: 77%
“…The concentration of trehalose, glycogen, glucose, adenosine in the hemolymph and fat body was determined by colorimetric methods using Trehalose Microplate Assay Kit (Cohesion Biosciences, Ltd., CAK1029), Glycogen Assay Kit (Cell Biolabs Inc., MET-5022), Glucose Assay Kit (Cell Biolabs Inc., STA-680), and Adenosine Assay Kit (Cell Biolabs Inc., MET-5090) respectively. Colorimetric methods using these commercially available kits have been established for insect samples in metabolic studies ( Chang et al., 2020 ; Lin et al, 2020 ). For each measurement, we added necessary positive and negative controls for color development according to the manufacturers' manuals to ensure the effectiveness of colorimetric assays.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the level of ATP in the samples, Molecular Probes® ATP Determination Kit (Invitrogen, A22066) was used as previously described ( Chang et al., 2020 ; Lin et al, 2020 ). Specifically, fat bodies or hemolymphs from larvae, or SL1A and BmN cells infected by the virus, were lysed with cell culture lysis reagent that contained 25 mM Tris-phosphate (pH 7.8), 2 mM 1,2-diaminocyclohexane-N,N,N’,N’-tetraacetic acid, 2 mM DTT, 10% glycerol, and 1% Triton® X-100.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the DWV genome copy number was significantly reduced in bees receiving the caffeine diet ( Figure 2 A), suggesting that caffeine induced the expression of immune response related genes, which in turn suppressed DWV genome replication. It is known that an optimal immune response requires a significant amount of energy [ 40 ]; therefore, we hypothesized that caffeine stimulates the expression of immune response-related genes by imposing positive effects on pathways relating to carbohydrate metabolism. To test this hypothesis, we analyzed the expression of genes involved in glycolysis and the tricarboxylic acid cycle (TCA) cycle in bees with or without the caffeine diet by real-time PCR ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%